Концептні імплікації у вивченні взаємозв'язку ідентифікації й ідентичності - Кубаєвський, Микола; Лук’яненко, Світлана; Kubayevskyi, Mykolа; Lukianenko, Svitlana (ТНЕУ, 2009)
У статті теоретично обґрунтовані концептно-методологічні засновки дослідження проблеми взаємозв’язку ідентифікації й ідентичності та проаналізовані їх функції у процесі соціалізації особистості. In the article the concept preconditions of the investigation of the problem of interconnection of identification and identity are theoretically based, their functions in the process of personality socialization are analyzed. Methodological key to its solution is, from one side, their substanti- ation in the context of higher contextually and meaningfully concepts “social” and “culture” and from another side – the use of principles of dialectical logics – movement of reasoning from single to general and from it – to peculiar. In the result two derivative implication lines of concept analysis: “identification – social – socialized personality” and “identification – culture – sociocultural identity” are realized
Concept Implications in Studying Interconnection of Identification and Identity
Keywords: концепт; культура; ідентифікація; ідентичність; метод; методологія; дискурс; дефініція; референт; означник; означуване; симулякр; постмодернізм; соціальне; знак; знання; переконання; мова; парадигма; соціалізація